Fabricators of the world scenarios of self-will ; Pawel Althamer and his class of objects/sculpture at the Academy of Fine Arts, Vienna, Franz Kapfer, L/B, Christian Philipp Müller, Maria Papadimitriou, Kateřina Šedá ; June 3 to October 31, 2010 ; X Regionale 10 ; [publ. on the occasion of the exhibition ... Schloss Trautenfels Universalmuseum Joanneum June 03 - October 31, 2010] - Budak, Adam 1966- (Universalmuseum Joanneum, 2010)
Pawel Althamer and his class of objects/sculpture at the Academy of Fine Arts, Vienna -- Franz Kapfer -- L/B -- Christian Philipp Müller -- Maria Papadimitriou -- Katerina Seda